Glucoregulatory disruption in male mice offspring induced by maternal transfer of endocrine disrupting brominated flame retardants in DE-71 - Kozlova, Elena V.; Chinthirla, Bhuvaneswari D.; Bishay, Anthony E.; Pérez, Pedro A.; Denys, Maximillian E.; Krum, Julia M.; DiPatrizio, Nicholas V.; Currás-Collazo, Margarita C. (Frontiers in Endocrinology, 2023)
Introduction Polybrominated diphenyl ethers (PBDEs) are commercially used flame retardants that bioaccumulate in human tissues, including breast milk. PBDEs produce endocrine and metabolic disruption in experimental animals and have been associated with diabetes and metabolic syndrome (MetS) in humans, however, their sex-specific diabetogenic effects are not completely understood. Our past works show glucolipid dysregulation resulting from perinatal exposure to the commercial penta-mixture of PBDEs, DE-71, in C57BL/6 female mice. Methods As a comparison, in the current study, the effects of DE-71 on glucose homeostasis in male offspring was examined. C57BL/6N dams were exposed to DE-71 at 0.1 mg/kg/d (L-DE-71), 0.4 mg/kg/d (H-DE-71), or received corn oil vehicle (VEH/CON) for a total of 10 wks, including gestation and lactation and their male offspring were examined in adulthood. Results Compared to VEH/CON, DE-71 exposure produced hypoglycemia after a 11 h fast (H-DE-71). An increased fast duration from 9 to 11 h resulted in lower blood glucose in both DE-71 exposure groups. In vivo glucose challenge showed marked glucose intolerance (H-DE-71) and incomplete clearance (L- and H-DE-71). Moreover, L-DE-71-exposed mice showed altered glucose responses to exogenous insulin, including incomplete glucose clearance and/or utilization. In addition, L-DE-71 produced elevated levels of plasma glucagon and the incretin, active glucagon-like peptide-1 (7-36) amide (GLP-1) but no changes were detected in insulin. These alterations, which represent criteria used clinically to diagnose diabetes in humans, were accompanied with reduced hepatic glutamate dehydrogenase enzymatic activity, elevated adrenal epinephrine and decreased thermogenic brown adipose tissue (BAT) mass, indicating involvement of several organ system targets of PBDEs. Liver levels of several endocannabinoid species were not altered. Discussion Our findings demonstrate that chronic, low-level exposure to PBDEs in dams can dysregulate glucose homeostasis and glucoregulatory hormones in their male offspring. Previous findings using female siblings show altered glucose homeostasis that aligned with a contrasting diabetogenic phenotype, while their mothers displayed more subtle glucoregulatory alterations, suggesting that developing organisms are more susceptible to DE-71. We summarize the results of the current work, generated in males, considering previous findings in females. Collectively, these findings offer a comprehensive account of differential effects of environmentally relevant PBDEs on glucose homeostasis and glucoregulatory endocrine dysregulation of developmentally exposed male and female mice.